2000
DOI: 10.1159/000016594
|View full text |Cite
|
Sign up to set email alerts
|

Digital Subtraction Radiography for Monitoring Dental Demineralization

Abstract: The aim of the present study was to evaluate the assessment of progression of demineralization by digital subtraction radiography. In each of 14 extracted human teeth, 2 approximal enamel demineralization lesions were induced in vitro to simulate dental caries. A modified tunnel preparation with glass ionomer fillings was performed on one lesion of every tooth as a model of caries inhibition. Every week, radiographs were obtained under standardized conditions over a period of 42 days. The radiographs were digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
(27 reference statements)
0
14
0
3
Order By: Relevance
“…This method was used in several previous studies to observe the progression of proximal lesion demineralization, 12 artificial recurrent caries, 14 root resorption, 15 and periodontal lesions. 16 Polishing with finer abrasives is necessary to achieve a subsequent reduction of grooves caused by coarse abrasives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was used in several previous studies to observe the progression of proximal lesion demineralization, 12 artificial recurrent caries, 14 root resorption, 15 and periodontal lesions. 16 Polishing with finer abrasives is necessary to achieve a subsequent reduction of grooves caused by coarse abrasives.…”
Section: Discussionmentioning
confidence: 99%
“…The films were developed, fixed, and dried in an automatic processor (XR 24 Nova; Dü rr-Dental, Bietigheim-Bissingen, Germany). After digitizing the radiographs at 1.000 dpi in grayscale mode with a scanner (UMAX Powerlook III, Willich, Germany), a digital subtraction analysis was conducted according to Eberhard et al 12 using the software Photoshop 7.0 (Adobe, San Jose, Calif) and NIH Image 1.34 (National Institutes of Health, Bethesda, Md).…”
Section: Digital Subtraction Radiographymentioning
confidence: 99%
“…However, if a carious lesion has progressed, the difference is seen as either an increase or decrease in pixel values on a more uniform background. By increasing the contrast in this image the caries signal is magnified so that changes can be detected more easily [Eberhard et al, 2000;Wenzel et al, 1993]. In practice, the method has limitations, not least of which is the requirement to maintain projection geometries as uniform as possible when capturing both radiographs.…”
mentioning
confidence: 99%
“…33,34 The capacity of several radiographic methods for the detection of different degrees of enamel demineralization was investigated as well. Nevertheless, they either used subtraction radiography to evaluate the resultant images for detection of enamel demineralization 12,14 or compared the performance of advanced diagnostic methods such as digital imaging fibre-optic transillumination or polarizationsensitive optical coherence tomography for the evaluation of the relationship between lesion depth and diagnostic accuracy. 35,36 Owing to the difficulties in combining quantitative methods for mineral determination and methods for obtaining the radiographic image of the same teeth for visual evaluation, no study can be found correlating the amount of calcium loss, lesion depth and the diagnostic accuracy of digital and conventional radiography for the detection of artificial enamel demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of different radiographic methods for the detection of enamel subsurface demineralization was compared previously by many researchers. [12][13][14][15] However, there is no study demonstrating the performance of different intraoral radiographic methods for the detection of artificial enamel demineralization in correlation with the amount of calcium loss and lesion depth. Therefore, the aim of this study was to determine the relationship between the amount of calcium loss, lesion depth and the diagnostic accuracy of the DigoraH Optime (Soredex Corporation, Tuusula, Finland) image plate system and F-speed film (Carestream Kodak, Rochester, NY) for the detection of approximal enamel subsurface demineralization.…”
Section: Introductionmentioning
confidence: 99%